Knowledge does not protect against illusory truth - Fazio, Lisa K; Brashier, Nadia M; Payne, B Keith; Marsh, Elizabeth J (Journal of experimental psychology. General, 2015)
In daily life, we frequently encounter false claims in the form of consumer advertisements, political propaganda, and rumors. Repetition may be one way that insidious misconceptions, such as the belief that vitamin C prevents the common cold, enter our knowledge base. Research on the illusory truth effect demonstrates that repeated statements are easier to process, and subsequently perceived to be more truthful, than new statements. The prevailing assumption in the literature has been that knowledge constrains this effect (i.e., repeating the statement "The Atlantic Ocean is the largest ocean on Earth" will not make you believe it). We tested this assumption using both normed estimates of knowledge and individuals' demonstrated knowledge on a postexperimental knowledge check (Experiment 1). Contrary to prior suppositions, illusory truth effects occurred even when participants knew better. Multinomial modeling demonstrated that participants sometimes rely on fluency even if knowledge is also available to them (Experiment 2). Thus, participants demonstrated knowledge neglect, or the failure to rely on stored knowledge, in the face of fluent processing experiences.